Sinergi Karang Taruna Boto Lempangang dan Mahasiswa KKN UINAM dalam Gelar Lomba Semarak Kemerdekaan 17 Agustus - Nurhikmah, Nurhikmah (Yayasan Abdurrauf Cendekia Nusantara, 2024)
The 17 August Independence Day lively competition in Lempangang Village was the result of a collaboration between Karang Taruna and the Real Work Lecture (KKN) students from Alauddin State Islamic University Makassar (UINAM) class of 75. This activity aims to commemorate the 79th Independence Day of the Republic of Indonesia in a creative way and full of togetherness. This article discusses the planning process, implementation, and results achieved from the activity, including its impact on the community. The results of the activity show that this collaboration has succeeded in increasing community participation, especially the younger generation, in commemorating Independence Day. The various competitions held have succeeded in creating a lively atmosphere and strengthening social ties between residents. In addition, this activity also provides learning about the importance of mutual cooperation and a sense of nationalism. Despite being faced with several obstacles such as weather conditions and limited facilities, the synergy between Karang Taruna Boto Lempangang and UINAM KKN students was able to overcome these challenges well. In conclusion, this collaboration has not only succeeded in enlivening the celebration of independence, but has also made a real contribution to strengthening the values ??of togetherness and nationalism in society. Keywords: Independence, Collaboration, Nationalism, Mutual Cooperation. Abstrak: Kegiatan lomba semarak kemerdekaan 17 Agustus di Desa Lempangang merupakan hasil dari kolaborasi antara Karang Taruna dan mahasiswa Kuliah Kerja Nyata (KKN) dari Universitas Islam Negeri Alauddin Makassar (UINAM) angkatan 75. Kegiatan ini bertujuan untuk memperingati Hari Kemerdekaan Republik Indonesia yang ke-79 dengan cara yang kreatif dan penuh semangat kebersamaan. Artikel ini membahas proses perencanaan, pelaksanaan, serta hasil yang dicapai dari kegiatan tersebut, termasuk dampaknya terhadap masyarakat. Hasil kegiatan menunjukkan bahwa kolaborasi ini berhasil meningkatkan partisipasi masyarakat, terutama generasi muda, dalam memperingati hari kemerdekaan. Berbagai lomba yang diselenggarakan berhasil menciptakan suasana yang meriah dan mempererat ikatan sosial antarwarga. Selain itu, kegiatan ini juga memberikan pembelajaran tentang pentingnya gotong royong dan rasa nasionalisme. Meski dihadapkan pada beberapa kendala seperti kondisi cuaca dan keterbatasan fasilitas, sinergi antara Karang Taruna Boto Lempangang dan mahasiswa KKN UINAM mampu mengatasi tantangan tersebut dengan baik. Kesimpulannya, kolaborasi ini tidak hanya berhasil memeriahkan perayaan kemerdekaan, tetapi juga memberikan kontribusi nyata dalam memperkuat nilai-nilai kebersamaan dan nasionalisme di masyarakat.